Public holidays effects on volatility in Shanghai stock exchange market - Ju, Luyao; Tanizaki, Hisashi (International Journal of Asian Social Science, 2024)
In this paper, we investigate the impact of China’s seven major public holidays on Shanghai Stock Exchange Composite Index daily returns’ volatility from January 4, 2002, to November 17, 2023. Utilizing the GARCH (1, 1) model, we aim to uncover whether there are the seven public holiday effects in addition to the well-known conventional holiday effects in stock returns’ volatility. There are a lot of research papers on the seven public holiday effects in the return level but few ones in the return volatility. Especially, we investigate both pre- and post-holiday effects in the seven major public holidays. As a result, we find that the pre-holiday effects are insignificant in most of the seven major public holidays, suggesting that investor behavior does not change significantly before the public holidays. In contrast, the post-holiday effects are significant in most of the seven major public holidays, indicating high volatility after the public holidays. Because the stock market is worldwide and operates continuously, the volatility of stock returns increases significantly when China’s stock market opens after the public holidays. Through these findings, inventors can better understand market volatility and the accompanying risks before and after the public holidays.